Incidencia de la inversión extranjera en el desarrollo empresarial Ecuatoriano en el período 20016-2011 - Carrera Rosero, Gabriela Alexandra (2013)
This work includes a study on the impact of foreign investment in Ecuador's business development. The conceptual context of foreign investment was investigated and the Ecuadorian enterprises with foreign investment contributions was chosen as population. Results from the survey were that foreign investment during the period 2006-2011 has been a major shift in prior periods governments adopted mechanisms to attract private foreign investment through the establishment of foreign companies.